2011
DOI: 10.1165/rcmb.2011-0023oc
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Antibody Therapy Attenuates Hyperoxia-Induced Lung Injury in Neonatal Rats

Abstract: Despite recent advances in neonatal intensive care and surfactant therapy, bronchopulmonary dysplasia (BPD) continues to be one of the most common long-term pulmonary complications associated with preterm birth. Clinical efforts to prevent and treat BPD have been largely unsuccessful due to its multifactorial nature and poorly understood disease process. Connective tissue growth factor (CTGF) is a matricellular protein that plays an important role in tissue development and remodeling. Previous studies have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 53 publications
2
69
3
Order By: Relevance
“…We showed here that the increased pulmonary vascularization and decreased vascular remodeling by β-catenin inhibition leads to decreased RVSP and RVH, suggesting decreased PH. These data are consistent with our previous studies in hyperoxia-induced neonatal lung injury model that treatment with CTGF-neutralizing antibodies and ICG001decreased PH (6,18). PH is often associated with severe BPD.…”
Section: Ctgf β-Catenin and Neonatal Lungsupporting
confidence: 93%
See 2 more Smart Citations
“…We showed here that the increased pulmonary vascularization and decreased vascular remodeling by β-catenin inhibition leads to decreased RVSP and RVH, suggesting decreased PH. These data are consistent with our previous studies in hyperoxia-induced neonatal lung injury model that treatment with CTGF-neutralizing antibodies and ICG001decreased PH (6,18). PH is often associated with severe BPD.…”
Section: Ctgf β-Catenin and Neonatal Lungsupporting
confidence: 93%
“…Activation of ILK and LRP5/6 can lead to nuclear translocation of β-catenin and subsequent activation of target gene transcription. We and others have previously demonstrated that β-catenin signaling is increased in the lungs of hyperoxia-exposed neonatal rats, a widely used experimental model of BPD (6,24). A recent study demonstrated that increased β-catenin is present in the mesenchymal stromal cells isolated from infants developing BPD and in α-SMA-positive myofibroblasts in the lungs of infants dying of BPD (25).…”
Section: Ctgf β-Catenin and Neonatal Lungmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, anti-CTGF therapy attenuates hyperoxia-induced alveolar damage and vascular remodeling (31). Multiple studies in kidney and liver have demonstrated that PTX downregulates the expression of CTGF (32,33); therefore, we expected that PTX would decrease CTGF expression and lung fibrosis during hyperoxia.…”
Section: Discussionmentioning
confidence: 96%
“…Pups were delivered naturally at term gestation, pooled, and randomly assigned to three groups to receive RA plus placebo, NS (RA + NS); hyperoxia (>95% O 2 ) plus NS (O 2 + NS); or hyperoxia plus PTX (O 2 + PTX; Aventis Pharma, Mexico City, Mexico). Hyperoxia was achieved in a sealed Plexiglas chamber as previously described (31). PTX (75 mg/kg equivalent to 3.75 ml/kg) based on the efficacy and safety data previously reported by ter Horst et al (21) or NS (same volume) was given via subcutaneous injection before O 2 exposure and then twice a day during continuous exposure to RA or O 2 for 4-9 d. Dams were rotated daily between RA and O 2 to avoid oxygen toxicity.…”
Section: Animal Model and Experimental Protocolmentioning
confidence: 99%